Immigrants and Unemployment in the European Community: From the Eyes of Natives - Ira N. Gang; Francisco L. Rivera-Batiz; Myeong-Su Yun (Institute for the Study of Labor (IZA), 1999)
This paper examines whether immigrants increase the likelihood of unemployment among native-born workers in the European Union. Earlier papers measure the presence of immigrants in the local labor market by computing the share of the foreigners in specific regions. This paper, instead, utilizes a unique feature of the 1988 Eurobarometer, which asks the native-born workers? assessment of the number of immigrants in the local market. By doing so, the association between unemployment of native-born workers in the European Union and presence of immigrants in the local labor market is evaluated from the native-born workers? own perspective. The empirical results indicate that there is little, if any, association between the presence of immigrants and unemployment among native-born workers.
Keywords: F22; J64; J61; 330; immigration; unemployment; education; Einwanderung; Internationale Arbeitsmobilität; Arbeitslosigkeit; Arbeitsmarkt; Humankapital; Schätzung; EU-Staaten; Frankreich; Deutschland; Italien; Niederlande; Großbritannien